2018
DOI: 10.1007/s40273-018-0711-9
|View full text |Cite
|
Sign up to set email alerts
|

Trusting the Results of Model-Based Economic Analyses: Is there a Pragmatic Validation Solution?

Abstract: Models have become a nearly essential component of health technology assessment. This is because the efficacy and safety data available from clinical trials are insufficient to provide the required estimates of impact of new interventions over long periods of time and for other populations and subgroups. Despite more than five decades of use of these decision-analytic models, decision makers are still often presented with poorly validated models and thus trust in their results is impaired. Among the reasons fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…When an analysis can be programmed in Excel and remain 'fit for purpose' in terms of computational efficiency and analytic transparency, there seems little benefit in moving to an alternative approach. Moving forward, increasing acceptance by external reviewers will be driven by increased training as part of health economics courses and using accepted and validated code for as many functionalities as feasible, with new analyses being well highlighted and documented [58].…”
Section: Discussionmentioning
confidence: 99%
“…When an analysis can be programmed in Excel and remain 'fit for purpose' in terms of computational efficiency and analytic transparency, there seems little benefit in moving to an alternative approach. Moving forward, increasing acceptance by external reviewers will be driven by increased training as part of health economics courses and using accepted and validated code for as many functionalities as feasible, with new analyses being well highlighted and documented [58].…”
Section: Discussionmentioning
confidence: 99%
“…the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) statement [12], which provides guidance on how to report economic evaluations more consistently and with transparency, and the Philips et al [13] checklist based on a review of guidelines for good practice in decision-analytic modelling for health technology assessment (HTA). Other authors have also suggested pragmatic steps to improve the validation of models [14].…”
Section: Vehicles For Cost-effectiveness Analysis (Cea): Within-trialmentioning
confidence: 99%
“…Our review identified some good examples where a model was further developed over time to address multiple reimbursement decisions (e.g. Birmingham Rheumatoid Arthritis Model [BRAM] [75,158], Tran-Duy model [68,122], Sheffield rheumatoid arthritis models [159], and the Advanced Simulation Model [78]). However, each was developed by the same research group.…”
Section: Health Technology Assessmentmentioning
confidence: 99%
“…In some models, when patients move quickly through the sequence of treatments (for example, early discontinuation due to adverse effects), simulated patients can actually benefit from having multiple 'short-term' benefits from different treatments, thus gaining an additive effect. Some included models of inflammatory arthritis attempted to overcome this problem by introducing a 'rebound' effect, which automatically returns the patient to their starting severity (used in, for example, the Diamantopoulos model [89]), or following some natural, background increase (as used in the BRAM [158]). Although the evidence to support this type of assumption is weak, it is arguably better than the false benefits generated by models otherwise.…”
Section: D) 'Single Point' a -B -C -D A -B -X -Dmentioning
confidence: 99%